KRIMINALISASI PENGGUNAAN KETAMINE SEBAGAI NARKOTIKA BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Alya Clara Angelita; Rugun Romaida Hutabarat (Fakultas Hukum Universitas Tarumanagara, 2022)
Ketamine is one of the anesthetic drugs that is still very commonly used by the medical world. Ketamine is asynthetic from class I narcotics, Phencyclidine (PCP). Used in the correct dosage according to a doctor'sprescription, ketamine is an ef ective way to replace Phencyclidine. The most obvious ef ect of the use ofKetamine is psychoactive, namely, causing loss of consciousness, pain relief, hallucinations, if used in thelong term and continuously with excessive doses can damage the brain nerves, dependence or addiction. Thisresearch uses normative juridical research by using research on legal systematics, besides that this researchuses positive legal regulations. The results of this study indicate that it is found that the use of ketamine isoften misused by the community, especially adolescents as a substitute for narcotics. Considering the ef ectsthat ketamine gives are hallucinogens and addiction, ketamine should be included in the regulation of theNarcotics Act, no longer included in the Health Act.